High-throughput sequencing reveals circular RNA hsa_circ_0000592 as a novel player in the carcinogenesis of gastric carcinoma. Issue 6 (28th June 2019) - Liang, Min; Liu, Zhaoyu; Lin, Hai; Shi, Boyun; Li, Ming; Chen, Ting; Qin, Lingyu; Niu, Qiuling; Yu, Guifang; Jiang, Hui; Zhou, Xinke
Abstract : Background/Aim: Gastric cancer is one of the most common malignant tumors, and its complex pathogenesis has not been fully elucidated. Circular RNAs (circRNAs) are involved in various biological processes and human diseases. However, their exact functional roles and mechanisms of action remain largely unclear. We previously discovered the differential expression of non-coding RNAs (ncRNAs) during the malignant transformation of human gastric epithelial cells. In this study, we investigated the functional roles of a significantly up-regulated circRNA (hsa_circ_0000592) in gastric cancer. Methods: N -methyl- N ′-nitro- N -nitrosoguanidine (MNNG)-induced malignant-transformed gastric epithelial cells (GES-1-T) and normal gastric epithelial cells (GES-1-N) were analyzed by high-throughput circRNA sequencing. The top 15 up-regulated circRNAs in high-throughput sequencing results were further confirmed by qRT-PCR in different gastric epithelial cell lines. The function of the most significant circRNA (hsa_circ_0000592) was investigated by using RNA interference (RNAi) assays, fluorescence in situ hybridization analysis (FISH), and bioinformatics prediction methods. Results: A total of 1509 genes were up-regulated and 3142 genes were down-regulated in GES-1-T cells when compared with GES-1-N cells. When compared with GES-1-N cells, hsa_circ_0000592 was obviously up-regulated in GES-1-T cells, as well as in other gastric cancer cell lines. The silencing of hsa_circ_0000592 mRNA led to a decrease in cell proliferation, cell cycle arrest at the G0/G1 phase, an increased rate of apoptosis, and a reduction in cell migration. Furthermore, FISH showed that hsa_circ_0000592 was mainly located in the cytoplasm, and a bioinformatics analysis suggested that hsa_circ_0000592 might function by sponging multiple miRNAs, and most notably four conserved miRNAs, including miR-139-3p, miR-200, miR-367-3p, and miR-33a-3p. Conclusion: This study is the first to identify hsa_circ_0000592 as a novel circRNA with a critical role in MNNG-induced gastric cancer. Due to the essential role of hsa_circ_0000592 in gastric carcinoma cells, it may be considered as a potential biomarker for use in diagnosing gastric carcinoma. Our findings provide a new insight into the function of circRNAs in environmental carcinogen-induced gastric cancer.